Cover Feature: Dimethyl Ether Oxidation on an Active SnO2/Pt/C Catalyst for High‐Power Fuel Cells (ChemElectroChem 9/2019). Issue 9 (16th April 2019) - Kashyap, Diwakar; Teller, Hanan; Schechter, Alex
Abstract : The Cover Feature shows a schematic of a dimethyl ether (DME)‐fueled polymer electrolyte fuel cell. A new type of platinum and platinum–tin alloy, supported on tin oxide and dispersed on an activated carbon anode catalyst (magnified section), provides high specific power output at low temperatures and ambient pressure for automotive applications. More information can be found in the Article by D. Kashyap et al onpage 2407 in Issue 9, 2019 (DOI:10.1002/celc.201900216 ).